Uttar Pradesh Development Report Volume 2 - Planning Commission (Planning Commission, 2007)
Agriculture sector is the prime mover of economic growth in Uttar Pradesh. A vast majority of the population in the state virtually relies on agriculture for its livelihood. As high as 65 per cent of the total workforce in the state depends on agriculture, most of whom are below poverty line.
Planning Commission Government of India
Planning Commission Government of India